Pengaruh Operating Cost And Operating Income, Non Performing Loan, and Loan To Deposit Ratio Terhadap Nilai Perusahaan Pada Bank Konvensional Bumn Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2019-2022 - Feisya Rianawati; Taufik Akbar; Karari Budi Prasasti (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This study aims to determine how the independent variables, namely Operating Cost and Operating Income, Non Performing Loan, and Loan to Deposit Ratio, influence the dependent variable, namely Company Value (Price to Book Value) in BUMN Conventional Banks listed on the IDX in 2019-2022. The type of research used is associative with a quantitative approach with a total population of 42 companies. The sampling technique uses purposive sampling so that the number of samples obtained is 4 companies. This study uses panel data regression analysis techniques using the help of Eviews 10 software. Based on the results of the study, it can be concluded that partially operating cost and operating income affect company value (Price to Book Value), while non-performing loans and loan to deposit ratios do not affect company value. Simultaneously operating cost and operating income, non-performing loans and loan to deposit ratios have a significant effect on company value (Price to Book Value).